2020
DOI: 10.20944/preprints202012.0533.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Anxiety – A Longitudinal Survey Study of Psychological and Situational Risks among Finnish Workers

Abstract: Background: COVID-19 crisis has changed the conditions of many throughout the globe. One negative consequence of the on-going pandemic is anxiety brought by uncertainty and the COVID-19 disease. Increased anxiety is a potential risk factor for wellbeing at work. This study investigated psychological, situational, and socio-demographic predictors of COVID-19 anxiety using longitudinal data. Methods: Nationally representative sample of Finnish workers (N = 1308) was collected before and during the COVID-19 crisi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
5
14
0
Order By: Relevance
“…The study found that there were significant differences in the level of social support at both times point of measurement. However, the level of social support was lower during the epidemic compare to the time when epidemic did not occur, which was consistent with previous researches (Savolainen et al, 2021). COVID-19 was a virus with high infectious rate and severe health consequences, which forced countries to deploy extreme measures to contain the spread.…”
Section: Discussionsupporting
confidence: 90%
“…The study found that there were significant differences in the level of social support at both times point of measurement. However, the level of social support was lower during the epidemic compare to the time when epidemic did not occur, which was consistent with previous researches (Savolainen et al, 2021). COVID-19 was a virus with high infectious rate and severe health consequences, which forced countries to deploy extreme measures to contain the spread.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, individuals who reported to partially work remotely and those who were working at the workplace had lower anxiety and depression levels and these factors were found to be protective against anxiety and depression, respectively. Accordingly, authors from Finland have reported higher COVID-19 anxiety in individuals who were working remotely during the pandemic due to the loss of social interaction in the workplace 31 . A study from Japan reported that partial remote work did not affect work productivity while full-remote work was shown to reduce work performance 32 .…”
Section: Discussionmentioning
confidence: 99%
“…11 Anxiety levels during a pandemic may be reduced when; the duration of isolation is as short as possible, the person receives accurate information, is informed by reliable means of communication, has sufficient supplies to decrease the frequency of going out, has a stable financial situation, engages in recreational/recreational activities, and when communication (physical or virtual) improves. 12 Due to fake news, people adopt various unwanted dietary and lifestyle modifications under the influence of rumors. These can adversely affect mental health.…”
Section: Discussionmentioning
confidence: 99%
“…13 Frequent inappropriate behaviors such as anger, restlessness, and worry about infection or possible infection with the virus that led people to post on social networks are observed. 12 People feel the need to talk to someone about their concerns related to the COVID-19 pandemic. Opportunities to vent their distress are limited in most of the population due to the emotionally blocked state.…”
Section: Discussionmentioning
confidence: 99%